IMPOTENSI SEBAGAI ALASAN FASAKH PRESPEKTIF IMAM AL-NAWAWI DAN IBNU HAZM : (STUDI KOMPARATIF) - Mustakim, Ahmad; Umami, Hafidhul; Mujib Ridwan, Abdul (USRATUNA: Jurnal Hukum Keluarga Islam, 2023)
A husband should not neglect his obligations, especially in regards to marital relations. If a husband neglects these obligations, it can have an impact on his wife and can lead to disputes between the two parties, even resulting in the dissolution of the marriage. The dissolution of a marriage can occur for various reasons, one of which is fasakh. The type of research used by the author is library research, using a qualitative approach. The primary sources in this study are the book of Imam al-Nawawi's Majmu' Syrh al-Muhaddab and the book of Ibn Hazm's al-Muhalla, while the secondary sources are obtained from literature related to the research problem. The data collection technique is done through documentation, while the data analysis uses content analysis which will then be compared to the opinions of the two imams. The results of this study are that according to Imam al-Nawawi, if a woman marries an impotent man, the wife is allowed to file for fasakh to the judge and the judge will give a one-year period. If within one year her husband can recover, then the wife remains a valid wife. However, after one year, if the husband does not recover, the wife is given the choice by the judge to either continue the marriage or dissolve it. If the wife is willing to accept her husband's condition, then she remains a valid wife, but if she is not willing to accept it, the judge will dissolve the marriage. Meanwhile, according to Ibn Hazm, in a marital relationship, if a defect is found in either the husband or wife, such as impotence, the marriage cannot be dissolved by fasakh due to the absence of valid evidence or nash, whether from the Qur'an, hadith, ijma', or al-dalil. The only way out if the husband is impotent is by talak pronounced by the husband. The result of the comparison of the opinions of the two imams is that impotence as a reason for fasakh according to Imam al-Nawawi is permissible based on the hadith narrated by Said bin Musayyab and the hadith narrated by Zaid bin Ka'ab. Meanwhile, Ibn Hazm argues that it is not permissible because he rejects the hadith narrated by Said bin Musayyab and the hadith narrated by Zaid bin Ka'ab.